Sensory predominant Guillain-Barré syndrome concomitant with dengue infection: A case report - Alvin Oliver Payus; Azliza Ibrahim; Liew, Constance Sat Lin; Tan, Hui Jan (S. Karger AG, 2022)
Guillain-Barre syndrome is an acute demyelinating polyneuropathy disease which is autoimmune in nature and usually follows gastrointestinal or respiratory infections. Dengue fever is however not a common trigger to the condition. Here, we report a patient who developed sensory predominant demyelinating polyradiculopathy during febrile phase of dengue fever. It was later confirmed with serology test and nerve conduction study. He was successfully treated with intravenous immunoglobulin and discharged home well. The purpose of this case report is to highlight that Guillain-Barré syndrome can occur as an uncommon neurological complication of dengue fever which can occur during any phase of the illness.